Quantitative 1H and 13C NMR and Chemometric Assessment of 13C NMR Data: Application to Anabolic Steroid Formulations - Stéphane Balayssac; Gaëtan Assemat; Saïda Danoun; Myriam Malet-Martino; Véronique Gilard (Molecules)
This study investigates the potential of 1H and 13C NMR for the characterization and classification of anabolic androgenic steroids (AASs) in various formulations. First, twenty AAS formulations, including tablets, capsules, and injectable solutions, were analyzed using 1H NMR for the qualitative identification and quantification of active compounds. The results revealed discrepancies between the labeled and detected substances in several samples, highlighting issues related to product mislabeling and potential health risks. Then, twelve oil-based injectable formulations were examined using 13C NMR, demonstrating its effectiveness in differentiating and quantifying closely related steroid structures that cannot be discriminated with 1H NMR. A chemometric approach from 13C NMR data, based on a principal component analysis (PCA) and hierarchical cluster analysis (HCA), enabled the classification of samples and the identification of key active ingredients.